Aplicação de transistores GAN FET, em um amplificador de áudio classe DDE 1KW - Alves, Allyfrahy Nunes (2021)
With recent advances in Gallium Nitride semiconductor technology (GaN) it was possible to obtain greater applications in the power electronics market, allowing high switching speeds and high densities of power conversion by transistors, in addition to decreasing the physical volumes of these components and their sinks. This work presents an application of Transistors GaNFETin the development of a class D audio amplifier of 1KW, this aims to observe its efficiency and losses generated in the switches. In this work is also carried out a small review of topologies used in class D amplifiers. The filter developed is of the 2° LC symmetrical Butterworth type, and the slation frequency is fixed at 400KHz. In the simulation, yield of 98.9% are obtained in the amplifier and in the Total Harmonic Distortion (THD) we obtained a result of 0.14% through the emulate transistor GaNFETTHP3212PS. In the physical prototype, two GaNFETLMG3411EVM-018 modules are used, and in nominal power yields of 98.6% are obtained. The calculated losses were 14.032W and the physical losses obtained in the amplifier were 14.236W. The signal/noise ratio is obtained by FFT of the output voltage at 1KHz presenting 57.2dB. The frequency response curve is presented with a typical feature for audio projects between 20Hz to 20kHz.